2020
DOI: 10.31838/jcr.07.02.38
|View full text |Cite
|
Sign up to set email alerts
|

Moonlighting Intentions of I.T. Professionals: Impact of Organizational Commitment and Entrepreneurial Motivation

Abstract: Moonlighting or double-jobbing is significantly on a rise in the current scenario of exclusive platform working specifically in Information Technology (I.T.) sector due to the widely prevailing flexible and alternative work-arrangements in this domain. There may be many purposes of moonlighting by the employees but financial strain is the most discussed and studied motive in the accessed literature. Nonpecuniary reasons are either meagrely discussed or theoritically studied. This paper aims to empirically stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…They found a significant negative relationship, suggesting that higher levels of organisational commitment can reduce the likelihood of employees engaging in moonlighting activities. Seema and Sachdeva (2020) study focused on the relationship between job satisfaction, organisational commitment, and moonlighting intentions among IT professionals. The findings revealed that organisational commitment mediated the relationship between job satisfaction and moonlighting intentions, emphasising the importance of job satisfaction and organisational commitment in reducing moonlighting intentions in the IT industry.…”
Section: Relationship Between Organisational Commitment and Moonlight...mentioning
confidence: 99%
See 3 more Smart Citations
“…They found a significant negative relationship, suggesting that higher levels of organisational commitment can reduce the likelihood of employees engaging in moonlighting activities. Seema and Sachdeva (2020) study focused on the relationship between job satisfaction, organisational commitment, and moonlighting intentions among IT professionals. The findings revealed that organisational commitment mediated the relationship between job satisfaction and moonlighting intentions, emphasising the importance of job satisfaction and organisational commitment in reducing moonlighting intentions in the IT industry.…”
Section: Relationship Between Organisational Commitment and Moonlight...mentioning
confidence: 99%
“…Moonlighting intentions were measured using a 7-item scale (e.g., "How often have you considered having a second job apart from your regular occupation?") which was developed by (Seema & Sachdeva, 2020). The Cronbach's alpha value for this scale is 0.938.…”
Section: Me Thodologymentioning
confidence: 99%
See 2 more Smart Citations
“…There is hard-hitting competition around the globe to survive the fittest. Human Resources's task is to build a win-win situation between employees and management to pursue personal development together with organizational development (Seema & Sachdeva, 2020).…”
Section: Hr Challengementioning
confidence: 99%